Ventos que cruzam o atlântico: intersecções, violência e subalternidade feminina na poética de Yaa Gyasi - Gomes, Paulo de Freitas (2024)
The objective of this research is to analyze female characters, highlighting the aspects of violence and subalternity, as an analytical category. The work examines the poetic performance of the African author, of Ghanaian origin, Yaa Gyasi. The aforementioned author uses the space of fiction and uses it as a tool to denounce the sociocultural imbalances caused by segregationist behaviors that aim at social fragmentation in order to preserve the status of supremacy. The intersection of indicators of subalternization, such as race, social class, gender, nationality and ethnic origin, are mechanisms used for the effective exercise of hegemonic institutions, legitimized by the patriarchal regime that gives the male entity decision-making power, leadership and moral authority over marginalized social layers. To consolidate the theoretical-argumentative measurements, we use the novel Homegoing (2017), as a corpus of analysis. The development of this thesis is relevant to the promotion of further studies in the field of literary theory, as well as expanding the critical-expository contributions related to post-colonial and gender reflexive interventions. In this way, we contribute to promoting the critical fortune inherent to the novelist Yaa Gyasi and provide, in the space of academic discussion, the products of her creative disposition. That said, in order to legitimize the argumentative assumptions and systematize the discussion, we resorted to the theoretical conjectures of AIDOO (1983, 2009), ACHOLONU (1995), AMADIUME (1987), ARNDT (2002), COLLINS (2019), DAVIS (2016), HUDSON-WEEMS (2020), BONNICI (2000), BHABHA (2014), BAMISILE (2021), ACHEBE (2012), ALENCASTRO (1998), MBEMBE (2014), APPIAH (2012), FANON (1968, 1983), among other epistemological frameworks necessary for the evolution of the thesis.